UJI STABILITAS DAN KEAMANAN GRANUL EKSTRAK BATANG SELEDRI (AVIUM GRAVEOLENS) SEBAGAI BIOLARVASIDA AEDES AEGYPTI - Dian Kartikasari; Dani Suryaningrat (As-Syifaa Jurnal Farmasi, 2020)
Long-term use of synthetic insecticides or larvicides can cause undesirable things, so plant-based biolarvacides need to be developed that do not cause harm and are more environmentally friendly. The aim of this study was to determine the total phenolic value of Avium graveolens  extract granules as well as to determine the temperature stability of good storage for larvicidal granules of Avium graveolens extract and to know the safe limits of the use of larvicide granules of Avium graveolens extract based on LC50 values. Total phenol test of Avium graveolens extract was carried out using Folin Cetaceau reagent, then the stability test of Avium graveolens extract granules was carried out by storing Avium graveolens extract granules at several different temperatures for the next 28 days based on physical properties and total phenol values on Avium graveolens extract granules before being saved and after being stored. Then the safety test was carried out by the BSLT method (Brine Shrimp Lethality Test) by looking at the number of deaths of Artemia saline larvae and then LC50 values were calculated.The results showed that the total phenol content of Avium graveolens extract was 0.23605% b / b. And the results of the stability test showed that the granules did not change physically even though they were stored at 60oC for 28 days. The results of the toxicity test obtained LC50 values of 608,98 mcg/g, meaning that Avium graveolens extract granules are safe to use